Assessment of the Competitiveness and Financial Sustainability of the Main Market Leaders in Customized Software in the Republic of Moldova - Cojocaru, Victor; Socoliuc, Marian (The Journal of Accounting and Management, 2024)
The purpose of this paper is to assess the financial position and performance of the main market leaders in the customized software sector in the Republic of Moldova for the period 2022-2023, based on the main financial indicators of their assessment. The research methodology consisted, in the first stage, in the manual collection of financial-accounting information from the financial statements published in the public depository of financial statements, in the second stage, this primary information was subjected to mathematical algorithms for determining financial indicators and which were subsequently used in economic-financial analysis. Our results revealed the specific trends associated with financial performance, competitiveness and sustainability as well as the determinants influencing the competitiveness and sustainability of the leaders in this sector. We believe that our results can be useful to investors who can guide their investments in companies in this sector, to the management of these companies who can base their management strategies on the results obtained, and to the state or regulatory bodies who can adopt public and fiscal policies specific to this sector.